A new heart surgery clinic: Open Heart Surgery Outcomes at Karabuk Training and Research Hospital: Assessment of the first year - Emre Kubat; Celal Selcuk Unal; Aydin Keskin; Emre Gok; Ufuk Turan Kursat Korkmaz; Umit Kervan; Mustafa Pac; Kasim Karapinar (Medicine Science, 2018)
This study aims to assess the one-year outcomes of open heart surgeries performed at the recently established Cardiovascular Surgery Clinic of Karabuk Training and Research Hospital. A total of 71 consecutive patients (60 males, 11 females; mean age 63.7±9.3 years; range 42 to 84 years) who underwent open heart surgery were evaluated retrospectively from 21 January 2016 to 21 January 2017. The most common comorbidity was hypertension (64.8%), followed by smoking (61.9%), chronic obstructive pulmonary disease (54.9%), and diabetes mellitus (40.6%). Mean length of stay at the intensive care unit was 3.4±2.9 days, and mean length of stay at the hospital was 10.4±6.9 days. In-hospital mortality occurred in a total of seven patients (9.9%). Early mortality (within the first 30 days) was seen in four (5.6%) patients. We believe our mortality and morbidity rates are acceptable despite the disadvantages of being a recently established center and the presence of multiple comorbid factors of patients. Although our clinic is a new center founded in Karabuk province, it is planned to become an important center in the future in terms of heart surgery through the increasing number and variety of surgeries. [Med-Science 2018; 7(1.000): 145-150]